FRAILTY TRAJECTORIES IN THE DECADE PRIOR TO DEATH AMONG U.S. VETERANS BORN 1927–1934. (16th November 2018) - Ward, R; Orkaby, A; Charest, B; Quach, L; Gagnon, D; Cho, K; Gaziano, J; Driver, J
Abstract: Studies have demonstrated that frailty predicts adverse outcomes such as mortality; however, few have characterized how frailty trajectories progress over time, particularly towards the end of life. In a nationwide retrospective cohort study, we characterized frailty trajectories over a 10-year period prior to death. Using VA electronic medical record data linked to Medicare/Medicaid (2002–2014), 31 age-related health deficits were used to calculate a frailty index annually. Death was determined by the National Death Index. Among 184, 235 regular VA users born from 1927–1934 (99.2% male, 90.2% white race), we described trajectories according to baseline chronic disease prevalence and time until death. Using cluster analysis, five trajectories were identified: 1) robust progressing to moderately frail (n=38, 203); 2) stable pre-frail (n=30, 680); 3) pre-frail progressing to moderately frail (n=31, 032); 4) mildly frail progressing to moderately frail (n=43, 709); and 5) mildly frail progressing to severely frail (n=40, 611). Mildly frail progressing to severely frail had the highest baseline prevalence of common chronic conditions (coronary artery disease 73.7%; arthritis 62.5%; peripheral vascular disease 52.0%; cerebrovascular disease 42.6%; cancer 30.5%; dementia 17.2%), while robust progressing to moderately frail had the lowest prevalence (coronary artery disease 23.5%; arthritis 27.4%; peripheral vascular disease 9.0%; cerebrovascular disease 7.2%; cancer 12.4%; dementia 2.3%). Mildly frail progressing to severely frail had the shortest time until death (5.7 years), while the stable pre-frail trajectory had the longest (8.6 years). Next steps will involve exploring key predictors of these 5 frailty trajectory patterns and causes of death.